2019
DOI: 10.1021/jacs.9b08914
|View full text |Cite
|
Sign up to set email alerts
|

General Base Swap Preserves Activity and Expands Substrate Tolerance in Hedgehog Autoprocessing

Abstract: Hedgehog (Hh) autoprocessing converts Hh precursor protein to cholesterylated Hh ligand for downstream signaling. A conserved active-site aspartate residue, D46, plays a key catalytic role in Hh autoprocessing by serving as a general base to activate substrate cholesterol. Here we report that a charge-altering Asp-to-His mutant (D46H) expands native cholesterylation activity and retains active-site conformation. Native activity toward cholesterol was established for D46H in vitro using a continuous FRET-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
(47 reference statements)
1
9
0
Order By: Relevance
“…Intriguingly, while we placed no constraints on the distance between the G197 oxyanion and the acidic proton of D243, these two atoms engaged in a 1.7 Å hydrogen bond over the course of equilibration (S6 Fig). This finding agrees with recent biochemical studies showing that a neutral D243 side chain stabilizes the oxyanion in during adduction, providing key insight into the mechanism of catalysis [53,54].…”
Section: Simulations Show a Dynamic Path To Adductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Intriguingly, while we placed no constraints on the distance between the G197 oxyanion and the acidic proton of D243, these two atoms engaged in a 1.7 Å hydrogen bond over the course of equilibration (S6 Fig). This finding agrees with recent biochemical studies showing that a neutral D243 side chain stabilizes the oxyanion in during adduction, providing key insight into the mechanism of catalysis [53,54].…”
Section: Simulations Show a Dynamic Path To Adductionsupporting
confidence: 91%
“…Importantly, formation of a covalent bond to the Hh protein requires the C3-OH of cholesterol to approach the C197-C198 thioester at an appropriate angle for orbital overlap. To guide cholesterol relocation, we used a modest force constant (0.48 kcal.mol -1 .Å -2 ) to place a distance constraint of 4 Å between C3-OH and D243 in the Hint fold active site (see Materials and Methods ) [ 12 , 53 , 54 ]. A movie of cholesterol’s migration to the active site during constrained dynamics analysis shows that conformational changes in the loop and HWY hinge at the back of the cholesterol pocket orient cholesterol for attack ( S2 Movie ).…”
Section: Resultsmentioning
confidence: 99%
“…The general base-swap D303H has been shown to preserve both structure and activity while also expanding substrate space in Hh autoprocessing ( Zhao et al, 2019 ). Using X-ray crystallography, D303H Hint domain ( Figure 6 , cyan ) was found to have an almost identical 3D structure compared to WT ( Figure 6 , red ) with an RMSD of 0.4 Å. NMR pH titration showed that H303 has the same p Ka as D303.…”
Section: Structural Mechanism Of Hedgehog Autoprocessingmentioning
confidence: 99%
“…Patched activation relieves its inhibition on Smoothened (SMO), another membrane protein, which turns on glioma-associated oncogene transcription factor (GLI) family of transcription factors to activate Hh signaling. Hh autoprocessing is important because it is at the origin of canonical Hh signaling, where it precedes all downstream signaling events ( Porter et al, 1996a ; Hall et al, 1997 ; Jiang and Paulus, 2010 ; Xie et al, 2014 ; Xie et al, 2015 ; Xie et al, 2016 ; Zhang et al, 2019 ; Zhao et al, 2019 ; Smith et al, 2020 ), and is unique to Hh proteins. Although it lies at the very origin of Hh signaling, there are only a few structural/mechanistic studies ( Owen et al, 2015a ; Owen et al, 2015b ; Callahan and Wang, 2015 ; Bordeau et al, 2016 ; Ciulla et al, 2018 ; Ciulla et al, 2019 ; Zhang et al, 2019 ; Zhao et al, 2019 ; Smith et al, 2020 ), compared to the great number of studies of downstream components, such as PTCH ( Ingham et al, 1991 ; Chen and Struhl, 1996 ; Sidransky, 1996 ; Kallassy et al, 1997 ; Xie et al, 1997 ; Zedan et al, 2001 ; Shao et al, 2006 ; Lorberbaum et al, 2016 ; Tukachinsky et al, 2016 ; Zhang et al, 2018 ; Abd Elrhman and Ebian, 2019 ; Kinnebrew et al, 2021 ), SMO ( Xie et al, 2014 ; Owen et al, 2015a ; Owen et al, 2015b ; Callahan and Wang, 2015 ; Xie et al, 2015 ; Xie et al, 2016 ; Zhang et al, 2019 ; Zhao et al, 2019 ; Smith et al, 2020 ), and GLI ( Lauth et al, 2007 ; Kim et al, 2010 ; Maun et al, 2010 ; Beauchamp et al, 2011 ; Pan et al, 2012 ; Long et al, 2016 ; Xiao et al, 2017 ; Kowatsch et al, 2019 ; Liu et al, 2019 ; Quagli...…”
Section: Introductionmentioning
confidence: 99%
“…The conserved Asp likely coordinates the binding of cholesterol to the SRR with the first step of autoprocessing, and activates the hydroxyl group of cholesterol to attack the thioester (Hall et al, 1997;Xie et al, 2016). Surprisingly, substitution of this Asp with His, a nominal charge reversal substitution (D46H in Drosophila HINT), can allow for a wider array of molecules, including coprostanol and epicoprostanol, to serve as the sterol substrate (Zhao et al, 2019). This is likely due to the more favorable, less spatially restrictive electrostatic stabilization of transition state provided by the H46 variant.…”
Section: Hedgehog Autoprocessing and Off-target Considerationsmentioning
confidence: 99%